2017
DOI: 10.1590/2317-1782/201720170022
|View full text |Cite
|
Sign up to set email alerts
|

Análises perceptivo-auditiva e acústica das vozes de crianças infectadas pelo HIV

Abstract: RESUMO Objetivo Comparar parâmetros vocais e acústicos de crianças infectadas e não infectadas pelo HIV (Vírus da Imunodeficiência Humana). Método Amostras vocais foram submetidas às análises perceptivo-auditiva e acústica. Foram analisadas amostras da vogal sustentada /ε/ e da fala encadeada de 74 crianças entre seis e 12 anos incompletos, divididas em dois grupos: 37 crianças infectadas pelo HIV (GHIV) e 37 crianças não infectadas pelo HIV (Grupo Controle=GC), pareadas por idade e gênero, e sem avaliação v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Pereira identified 34.4% of vocal nodules among dysphonic teachers. 15 A high rate of vocal nodules (43.87%) was also found in the present study. It is noteworthy that both midposterior triangular chink and double chink, findings of the present study, are generally related to the presence of vocal nodules and to musculoskeletal tension syndrome, and the literature shows that the midposterior triangular chink precedes the formation of vocal nodules.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pereira identified 34.4% of vocal nodules among dysphonic teachers. 15 A high rate of vocal nodules (43.87%) was also found in the present study. It is noteworthy that both midposterior triangular chink and double chink, findings of the present study, are generally related to the presence of vocal nodules and to musculoskeletal tension syndrome, and the literature shows that the midposterior triangular chink precedes the formation of vocal nodules.…”
Section: Discussionsupporting
confidence: 87%
“…The literature on this topic is vast, but most researches are restricted to the analysis of answers contained in questionnaires filled out by teachers. Few studies 15 cover vocal screening in the work environment and videolaryngoscopy exams for the diagnosis and preventive actions.…”
Section: Introductionmentioning
confidence: 99%
“…Estas alterações podem determinar prejuízo nas funções de mastigação e deglutição, favorecendo a ocorrência da disfagia. A disfagia é um sintoma secundário a uma doença de base que pode levar o indivíduo ao regurgitamento nasal; voz molhada; tosse e broncoaspiração de saliva e/ou alimento; o que pode refletir na recusa alimentar, resultando em desnutrição, desidratação e pneumonias de repetição [9][10][11][12] .…”
Section: Manifestações Orais Dificuldades Alimentares E Disfagiaunclassified
“…Enquanto isso, estudos descritivos posteriores, consideram possível o comprometimento a orelha interna, decorrente da própria ação do vírus HIV é mencionado em estudos envolvendo pacientes com SIDA, assim como a alteração auditiva ocasionada pelo uso de tratamento antirretroviral e medicações ototóxicas, ambos ocasionando perdas auditivas do tipo neurossensorial e, consequentemente, danos irreversíveis à orelha interna. E em relação ao comprometimento de orelha média e, consequentemente, a presença de perda auditiva condutiva ou mista, foi relatado que esta alteração seria decorrente da imunossupressão, que favorece a presença de infecções oportunistas 10 .…”
Section: Alterações Auditivasunclassified
“…Dear Editor, the publication on "Auditory-perceptual and acoustic analysis of voices of HIV-infected children" is very interesting (1) . Pereira et al concluded that "HIV-infected children presented similar vocal quality to children without the illness, both for the perceptual-auditory and acoustic evaluation" (1) . In fact, the vocal quality of children should not be different regardless of HIV infected status.…”
Section: Letter To the Editorsmentioning
confidence: 99%